Da'wah Through Thinking Skills According to The Perspective of The Quran - Tengku Husna Tengku Jamil; Hasanah Abd Khafidz; Khazri Osman (USIM Press, 2024)
Vol. 24 No. 1 (2021): Journal of Islamic Social Sciences and Humanities